The Nashob-Ed Isim In Surah Muhammad And Learning Techniques For Beginners - Hanafi, Deva; Thoyyibah, Idza Zuliyana; Muna, Revi Rifatul; Nabila, Aliya; Sunarko, Asep (DAS Institute, 2023)
This research aims to determine the sacred contents of Surah Muhammad and determine the most appropriate learning techniques for students at the initial level. This research uses a qualitative approach with a literature research type. Data analysis in this study used the Milles and Huberman technique. Based on data analysis that has been carried out, the Isim-s which are enshrined in Surah Muhammad is mentioned in each verse in the form maf'ul bih, maf'ul absolute, dhorof, tamyiz, isim la, munada, khobar kana waakhowatuha, isim inna waakhowatuha, and tawabi' so that the learning technique cooperative learning is suitable for studying it.